2018
DOI: 10.4103/jhrs.jhrs_47_17
|View full text |Cite
|
Sign up to set email alerts
|

Intracytoplasmic sperm injection with assisted oocyte activation resulting in successful pregnancies and live birth in couples with globozoospermia: A report of two cases

Abstract: Globozoospermia, characterized by round-headed acrosomeless sperm, is a rare and severe form of teratozoospermia. We report a successful pregnancy in two cases of total globozoospermia after intracytoplasmic sperm injection (ICSI) with oocyte activation with calcium ionophore. In thefirst case, globozoospermia was diagnosed on the day of oocyte retrieval. Among 11 retrieved oocytes, only one fertilized after ICSI. The pregnancy test 2 weeks after embryo transfer was negative. Two months later, the patient unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Thirdly, sperm aneuploidies can also affect ICSI outcomes. Increased aneuploidy rates often occur in acrocentric (13, 14, 15, 18 and 21) and sex chromosomes in globozoospermic rather than in fertile men (Carrell et al, , ; Dirican, Isik, Vicdan, Sozen, & Suludere, ; Kochhar & Ghosh, ). However, these findings have not yet been confirmed by other studies (Rybouchkin et al, ; Vicari et al, ).…”
Section: Fertilisation Potential and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, sperm aneuploidies can also affect ICSI outcomes. Increased aneuploidy rates often occur in acrocentric (13, 14, 15, 18 and 21) and sex chromosomes in globozoospermic rather than in fertile men (Carrell et al, , ; Dirican, Isik, Vicdan, Sozen, & Suludere, ; Kochhar & Ghosh, ). However, these findings have not yet been confirmed by other studies (Rybouchkin et al, ; Vicari et al, ).…”
Section: Fertilisation Potential and Treatmentsmentioning
confidence: 99%
“…Successful ART outcomes by resorting to some new treatment protocols/techniques along with ICSI, such as ICSI with AOA using calcium ionophore, may help overcome male infertility in patients with total globozoospermia (Abadi, Tavalaee, Shahverdi, & Nasr‐Esfahani, ; Karaca et al, ; Kochhar & Ghosh, ; Shang et al, ; Tavalaee et al, ). Some candidate genes such as truncated Kit, PLC ζ and post‐acrosomal sheath WW domain‐binding protein (PAWP) are found to be responsible for oocyte activation during fertilisation (Abadi et al, ; Haghighat et al, ; Tavalaee & Nasr‐Esfahani, ).…”
Section: Fertilisation Potential and Treatmentsmentioning
confidence: 99%
“…The first one is more frequent, it consists of a mixture of sperm anomalies referred to as polymorphic teratozoospermia. The second variety is characterised by a specific phenotype that affects most spermatozoa referred to as syndromic teratozoospermia such as globozoospermia, macrozoospermia or dysplasia of the fibrous sheath recently referred as MMAF (multiple morphological abnormalities of the sperm flagellum) (Carrell, Wilcox, Udoff, Thorp, & Campbell, ; Ghedir et al, ; Kochhar & Ghosh, ; Tavalaee, Nomikos, Lai, & Nasr‐Esfahani, ). Various studies have found out that patients with syndromic teratozoospermia show numerous nuclear alterations, namely abnormal chromatin structure, DNA fragmentation and aneuploidy (Ghedir et al, ; Perrin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fertilization failure has been reported to occur in 1-5% of human in vitro fertilization (IVF) cycles after intracytoplasmic sperm injection (ICSI) (1). Most of these cases resulted from poor sperm morphology, such as globozoospermia (2)(3)(4)(5). Globozoospermia is a rare form of teratozoopermia, mainly characterized by round-headed sperm that do not have or have very low level of phospholipase C-ζ (PLCζ), an important physiological agent inside sperm needed to induce oocyte activation (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Artificial oocyte activation (AOA) is a method of mimicking the physiological cell signaling mechanisms to activate oocytes, and calcium ionophore A23187 is the most widely used AOA method in humans (2)(3)(4)(8)(9)(10)(11)(12). Deliveries of healthy babies have been reported since AOA by calcium ionophore was adopted (2)(3)(4)(9)(10)(11)(12). A systematic review of published reports demonstrated acceptable outcomes of calcium ionophore use, particularly for couples in which ICSI alone yielded poor or no fertilization (11).…”
Section: Introductionmentioning
confidence: 99%